2016
DOI: 10.1158/1078-0432.ccr-13-1333
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pathways: Isocitrate Dehydrogenase Mutations in Cancer

Abstract: IDH1 and IDH2 are homodimeric enzymes that catalyze the conversion of isocitrate to α-ketoglutarate (α-KG) and concomitantly produce reduced nicotinamide adenine dinucleotide phosphate (NADPH) from NADP+. Mutations in the genes encoding IDH1 and IDH2 have recently been found in a variety of human cancers, most commonly glioma, acute myeloid leukemia (AML), chondrosarcoma, and intrahepatic cholangiocarcinoma. The mutant protein loses its normal enzymatic activity and gains a new ability to produce the ‘oncometa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
142
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(143 citation statements)
references
References 71 publications
0
142
0
1
Order By: Relevance
“…As mentioned above, the IDH mutation in gliomas has considerable prognostic implications, where mutated LGG patients live ~ 2.3× longer [45] and mutated GBM patients live ~ 2.0–3.5× longer [17, 45] than IDH1 WT patients. Emerging evidence suggests that these tumors co-opt numerous different biological processes compared to their WT counterparts [18, 2023]. One of these differentially adapted processes is tumor cell invasion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, the IDH mutation in gliomas has considerable prognostic implications, where mutated LGG patients live ~ 2.3× longer [45] and mutated GBM patients live ~ 2.0–3.5× longer [17, 45] than IDH1 WT patients. Emerging evidence suggests that these tumors co-opt numerous different biological processes compared to their WT counterparts [18, 2023]. One of these differentially adapted processes is tumor cell invasion.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly identified mutation is the IDH1 R132H gain-of-function mutation, which catalyzes the NADPH dependent reduction of α-ketoglutarate (α-KG) to produce the R enantiomer of 2-hydroxyglutarate (2-HG) [19]. In turn, 2-HG inhibits α-KG-dependent dioxygenases, with resultant downstream effects that mediate tumor cell interactions with the environment, collagen modification, responses to hypoxia, and immune evasion [18, 2023]. IDH1 mutant GBMs are more likely to involve the frontal lobes, demonstrate less contrast enhancement, and produce less peritumoral changes on MRI [24].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies revealed that IDH1 mutations occur in more than 70% of low grade gliomas and up to 20% of higher grade tumors (secondary glioblastoma multiforme; GBM), and approximately 10% of AML cases (3), 10% of cholangiocarcinoma (4), as well as in melanomas (5) and chondrosarcomas (6). Additionally, mutations were also identified in IDH2, the mitochondrial homolog of IDH1, in about 4% of gliomas and 10% of AMLs (3, 7). Nearly all known IDH1/2 alterations are heterozygous missense mutations that confer a neomorphic activity on the encoded enzymes, such that they convert α-KG to (R)-2HG (8).…”
Section: Introductionmentioning
confidence: 99%
“…In lower-grade glioma, an analysis of clonality also suggests that IDH1 mutation is among the earliest events, and occurs before TP53 mutation in astrocytomas or loss of 1p/19q in astrocytomas and oligodendrogliomas (1821). Based on these findings a series of mutant IDH1 inhibitors have been developed and are in clinical testing (22, 23). …”
Section: Introductionmentioning
confidence: 99%